Road Users in Road Traffic Fatalities in South Africa: Challenges and Effective Responses - Modipa, Mmakwena (Department of Public Administration, 2024)
Approximately 1.3 million people die each year as a result of road traffic crashes (World Health Organization, 2022). Furthermore, road traffic injuries are the leading cause of death for children and young adults aged 5-29 years, with more than half of all road traffic deaths occurring among vulnerable road users: pedestrians, cyclists, and motorcyclists. Young people pose a significant risk on the road globally, including in South Africa, where negligent driving is prevalent, putting other road users at risk of fatalities. Road traffic fatalities are a pressing issue for road traffic authorities in South Africa, with increasing numbers of fatalities. The inability of young people to adhere to road rules contributes to this high rate of road traffic fatalities. This article focuses on the challenges associated with young road users in road traffic fatalities and employs a qualitative methodology drawing on a wide range of secondary sources. It further utilizes findings from around the world to address these challenges. The research identifies key steps to prevent road traffic fatalities among young people, including strengthening law enforcement, conducting road safety awareness campaigns, combating corruption at driving license testing centers, and ensuring licenses are awarded based on competency rather than corrupt practices.